Power Dynamics in EFL, ESL, ELF A Metaphorical Adaptation of the Newtonian System - Sulindra, Eric; Cendra, Anastasia Nelladia; Hartani, Tuti (English Education and Literature Journal (E-Jou), 2025)
Understanding the power dynamics among English as a Foreign Language (EFL), English as a Second Language (ESL), and English as a Lingua Franca (ELF) is critical to navigate balanced English language education framework and policies which in turns would equalize global communication needs and local cultures preservation. This paper explains how the metaphorical perspective works in the context of EFL, ESL and ELF power dynamics and how these powers relate to one another, creating a power dynamics equilibrium and influencing greatly the global Englishes. Using a conceptual paper design in nature, the paper employs a metaphorical perspective of Newtonian System as opposing forces balancing each other to analyze the power dynamics of EFL, ESL and ELF. The Newtonian System metaphor provides an appropriate framework to describe the power equilibrium in the dynamics. On one side, factors like socioeconomic influences, demographic shifts, language policy, act metaphorically as forces pushing the spread of English across diverse contexts. Countries with strong economic ties to English-speaking nations tend to adopt ESL or EFL, driven by necessity (metaphorical representation of Newton’s first law of inertia). Simultaneously, the standard English paradigm acts as a force of conformity, reinforcing global norms and expectations around English usage, much like a gravitational pull, shaping the trajectories of EFL and ESL toward a fixed center of linguistic authority (metaphorical representation of Newton’s second law). On the opposite side, resistance arises from localized cultures, native languages, and distinct educational policies that push back, creating a dynamic balance similar to Newton’s third law of action and reaction. Future research can study extended contexts such as digital communication or postcolonial settings, to explore how local resistance adapts to globalization. Another possible further research are empirical investigations to recommend policy-making and teaching strategies that respect linguistic diversity while fostering global connectivity